Advanced Data Mining and Applications 19th International Conference, ADMA 2023, Shenyang, China, August 21-23, 2023, Proceedings, Part II - Yang, Xiaochun; Suhartanto, Heru.; Wang, Guoren; Wang, Bin.; Jiang, Jing.; Li, Bing.; Zhu, Huaijie; Cui, Ningning (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book constitutes the refereed proceedings of the 19th International Conference on Advanced Data Mining and Applications, ADMA 2023, held in Shenyang, China, during August 21-23, 2023. The 216 full papers included in this book were carefully reviewed and selected from 503 submissions. They were organized in topical sections as follows: Data mining foundations, Grand challenges of data mining, Parallel and distributed data mining algorithms, Mining on data streams, Graph mining and Spatial data mining.
Knowledge Graph -- Improving Distance Based Knowledge Graph Embedding via Contrastive Learning -- Knowledge Graph Completion with Information Adaptation and Refinement -- Duet Representation Learning with Entity Multi-Attribute Information in Knowledge Graphs -- TKGAT: Temporal Knowledge Graph Representation Learning Using Attention Network -- Separate-and-Aggregate: A Transformer-based Patch Refinement Model for Knowledge Graph Completion -- Two Birds With One Stone: An Link Prediction Model for Knowledge Hypergraph Based on Fully-Connected Tensor Decomposition -- HEM: an improved parametric link prediction algorithm based on hybrid network evolution mechanism -- Joint embedding of local structures and evolutionary patterns for temporal link prediction -- Multimedia -- DQN-based Stitching Algorithm for Unmanned Aerial Vehicle Images -- HM-QCNN: Hybrid Multi-branches Quantum-Classical Neural Network for image classification -- DetOH: An Anchor-free Object Detector with Only Heatmaps -- LAANet: An Efficient Automatic Modulation Recognition Model Based on LSTM-Autoencoder and Attention Mechanism -- A Compact Phoneme-To-Audio Aligner for Singing Voice -- Song-to-Video Translation: Writing a Video from Song Lyrics Based on Multimodal Pre-Training -- Medical Image Analysis -- Breast Cancer Histopathology Image Classification Using Frequency Attention Convolution Network -- Wavelet-SVDD: Anomaly Detection and Segmentation with Frequency Domain Attention -- Anatomical-Functional Fusion Network for Lesion Segmentation using Dual-view CEUS -- SpMVNet: Spatial Multi-view Network for Head and Neck Organs at Risk Segmentation -- SNN-BS: A Clinical Terminology Standardization Method using Siamese Networks with Batch Sampling Strategy -- Natural Language -- Read then Respond: Multi-granularity Grounding Prediction for Knowledge-Grounded Dialogue Generation -- SUMO-PEGASUS: A Two-Stage Model for Long Text Summarization -- An Extractive Automatic Summarization Method for Chinese Long Text -- A Likelihood Probability-based Online Summarization Ranking Model -- Spatial Commonsense Reasoning for Machine Reading Comprehension -- Multimodal learning for Automatic Summarization: A Survey -- Deep Knowledge Tracing with Concept Trees -- Privacy and Security -- Cryptography-Inspired Federated Learning for Generative Adversarial Networks and Meta Learning -- A Hessian-Based Federated Learning Approach to tackle Statistical Heterogeneity -- Analyzing the Convergence of Federated Learning with Biased Client Participation -- Privacy Lost in online Education: Analysis of Web Tracking Evolution -- DANAA: Towards transferable attacks with double adversarial neuron attribution -- CRNN-SA: A Network Intrusion Detection Method Based on Deep Learning -- Applications -- Conspiracy Spoofing Orders Detection with Transformer-based Deep Graph Learning -- A Novel Explainable Rumor Detection Model with Fusing Objective Information -- VLS: A Reinforcement Learning-based Value Lookahead Strategy for Multi-product Order Fulfillment -- Deep Reinforcement Learning for Stock Trading with Behavioral Finance Strategy -- Ensemble Learning based Employment Recommendation under Interaction Sparsity for College Students -- How does ChatGPT Affect Fake News Detection Systems? -- CNGT: Co-attention Networks with Graph Transformer for Fact Verification -- Multi-Modal -- Supervised Discriminative Discrete Hashing for Cross-modal Retrieval -- A Knowledge-enhanced Inferential Network for Cross-modality Multi-hop VQA -- Multi-Head Similarity Feature Representation and Filtration for Image-Text Matching -- Multimodal Conditional VAE for Zero-shot Real-world Event Discovery -- MAMRP: Multi-modal Data Aware Movie Rating Prediction -- MFMGC: A Multi-Modal Data Fusion Model for Movie Genre Classification -- TED-CS: Textual Enhanced Sensitive Video Detection with Common Sense Knowledge.
Keywords: Data mining; Artificial intelligence; Application software; Computer systems; Education -- Data processing; Computer vision; Data Mining and Knowledge Discovery; Artificial Intelligence; Computer and Information Systems Applications; Computer System Implementation; Computers and Education; Computer Vision